Evidence for a Sympatric Origin of Ribolla gialla, Gouais Blanc and Schiava cultivars (V. vinifera L.) - de Lorenzis, G.; Imazio, S.; Brancadoro, L.; Failla, O.; Scienza, A. (South African Journal of Enology and Viticulture, 2016)
Ribolla gialla is an autochthonous grape variety cultivated in Friuli Venezia Giulia (Italy) and in Slovenia, and probably originated in Eastern Central Europe. Just like Ribolla gialla, the Gouais blanc and Schiava cultivars also appear to have originated in the same geographical area. To verify this hypothesis, a pool of varieties probably sharing the same historical and geographical origin were taken into account. The fingerprinting, by 35 SSR loci, of Gouais blanc, Ribolla gialla, Schiava grossa and Schiava lombarda (synonyms of Schiava bresciana), is presented and the correlation among historical, geographical and genetic information of these cultivars was investigated. Gouais blanc and Traminer, already suggested as key varieties in the development of European grape diversity and as parents for some French varieties, interestingly enough seems to be linked to Ribolla gialla. The putative parentage was verified using 58 microsatellite markers. The genetic results suggest a common geographical origin for Gouais blanc, Ribolla gialla and the Schiava group: these cultivars appear to be related through sympatric origin. The hypothesis of Ribolla gialla as a progeny of Gouais blanc and Traminer was ruled out. The data proved a second-degree relationship between Gouais blanc and Ribolla gialla and a third or more distant degree of relationships between Ribolla gialla and Traminer.